Virtual defense. - Adams, James (Foreign Affairs)
Although the United States may be an uncontested military superpower, it remains defenseless against information warfare. As the military, private sector, and Washington grow increasingly dependent on computers and information networks, they also grow more susceptible to cyber-attack. Seeking to avoid a direct military encounter with U.S. forces, potential foreign aggressors now look instead to attacking the soft American underbelly, the private sector. Moreover, such attack make military retaliation very hard, either because the attack's origin is unknown or because the perpetrators have sabotaged civilian or military command networks. No mechanism currently exists to effectively defend the computer networks of businesses, the power grids of American cities, or even the information networks of the federal government; cyber-defense is in the hands of the FBI, a law-enforcement agency designed to pursue criminals, not defend the nation.